Guest

19. If a and p are the roots of the equation 2x² – 3x – 6 = 0. The equation whose roots are 1α and 1β is (a) 6x² – 3x + 2 = 0 (b) 6x² + 3x – 2 = 0 (c) 6x² – 3x – 2 = 0 (d) x² + 3x-2 = 0

19. If a and p are the roots of the equation 2x² – 3x – 6 = 0. The equation whose roots are 1α and 1β is
(a) 6x² – 3x + 2 = 0
(b) 6x² + 3x – 2 = 0
(c) 6x² – 3x – 2 = 0
(d) x² + 3x-2 = 0

Grade:12th pass

1 Answers

Pawan Prajapati
askIITians Faculty 60796 Points
one year ago
Answer: b

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free